Centro de Aprendizaje Tumul K'in: experiencia Educativa Formal. Belice - Rubén Requena, Oscar (2007)
This article is the result of the paper Tumul K'in Learning Center. This center is a place where a program for rural youth, especially for Mayan people, is developed. The author describes how the program helps young people that have not had access to secondary education.